Expression and Activation of BKCa Channels in Mice Protects Against Ischemia-Reperfusion Injury of Isolated Hearts by Modulating Mitochondrial Function - Goswami, Sumanta Kumar; Ponnalagu, Devasena; Hussain, Ahmed T.; Shah, Kajol; Karekar, Priyanka; Gururaja Rao, Shubha; Meredith, Andrea L.; Khan, Mahmood; Singh, Harpreet (Frontiers in Cardiovascular Medicine, 2019)
Aims Activation and expression of large conductance calcium and voltage-activated potassium channel (BKCa) by pharmacological agents have been implicated in cardioprotection from ischemia-reperfusion (IR) injury possibly by regulating mitochondrial function. Given the non-specific effects of pharmacological agents, it is not clear whether activation of BKCa is critical to cardioprotection. In this study, we aimed to decipher the mechanistic role of BKCa in cardioprotection from IR injury by using genetically activating BKCa channels. Methods and Results Hearts from adult (3 months old) wild-type mice (C57/BL6) and mice expressing genetically activated BKCa (Tg-BKCaR207Q, referred as Tg-BKCa) along with wild-type BKCa were subjected to 20 min of ischemia and 30 min of reperfusion with or without ischemic preconditioning (IPC, 2 times for 2.5 min interval for each). Left ventricular developed pressure (LVDP) was recorded by Millar’s Mikrotip® catheter connected to ADInstrument data acquisition system. Myocardial infarction was quantified by 2,3,5-triphenyl tetrazolium chloride (TTC) staining. Our results demonstrated that Tg-BKCa mice are protected from IR injury, and BKCa also contributes to IPC-mediated cardioprotection. Cardiac parameters were also measured by echocardiography and no differences were observed in left ventricular ejection fraction, fractional shortening and aortic velocities. Amplex Red® was used to assess reactive oxygen species (ROS) production in isolated mitochondria by spectrofluorometry. We found that genetic activation of BKCa reduces ROS after IR stress. Adult cardiomyocytes and mitochondria from Tg-BKCa mice were isolated and labeled with Anti-BKCa antibodies. Images acquired via confocal microscopy revealed localization of cardiac BKCa in the mitochondria. Conclusions Activation of BKCa is essential for recovery of cardiac function after IR injury and is likely a factor in IPC mediated cardioprotection. Genetic activation of BKCa reduces ROS produced by complex I and complex II/III in Tg-BKCa mice after IR, and IPC further decreases it. These results implicate BKCa-mediated cardioprotection in part by reducing mitochondrial ROS production. Localization of Tg-BKCa in adult cardiomyocytes of transgenic mice was similar to wild-type mice.